Parents' experiences of living with a child with a long‐term condition: a rapid structured review of the literature - Smith, Joanna (Health Expect, 2013)
BACKGROUND: Living with a child with a long‐term condition can result in challenges above usual parenting because of illness‐specific demands. A critical evaluation of research exploring parents' experiences of living with a child with a long‐term condition is timely because international health policy advocates that patients with long‐term conditions become active collaborators in care decisions. METHODS: A rapid structured review was undertaken (January 1999–December 2009) in accordance with the United Kingdom Centre for Reviews and Dissemination guidance. Three data bases (MEDLINE, CINAHL, PSYCINFO) were searched and also hand searching of the Journal of Advanced Nursing and Child: Care, Health and Development. Primary research studies written in English language describing parents' experiences of living with a child with a long‐term condition were included. Thematic analysis underpinned data synthesis. Quality appraisal involved assessing each study against predetermined criteria. RESULTS: Thirty‐four studies met the inclusion criteria. The impact of living with a child with a long‐term condition related to dealing with immediate concerns following the child's diagnosis and responding to the challenges of integrating the child's needs into family life. Parents' perceived they are not always supported in their quest for information and forming effective relationships with health‐care professionals can be stressful. Although having ultimate responsibility for their child's health can be overwhelming, parents developed considerable expertise in managing their child's condition. CONCLUSION: Parents' accounts suggest they not always supported in their role as manager for their child's long‐term condition and their expertise, and contribution to care is not always valued.